Pengaruh pemberian klonidine 75 μg oral pre operatif terhadap tramadol hydrochloride 2.5mg/kgbb/iv untuk penatalaksanaan nyeri paska bedah - Andri Faizal L; Hasanul Arifin; Syamsul Bahri (Majalah Kedokteran Nusantara The Journal Of Medical School, 2013)
Introduction : Post surgical pain is an important problem in the process of operation, so that a strong analgesia is needed in the post-surgery. Already popular opioid used as an analgesic tramadol hydrochloride one, but use a single dose require large doses resulting in severe side effects. Preemptive method is one method to produce a satisfactory analgesia. In this study aimed to compare the combination of tramadol hydrochloride 2.5mg / kg / IV and oral clonidine 75•g for pain management after orthopedic surgery extremities.Methods : After the approval of the ethics committee of FK-USU, 45 samples were collected, men and women, from the age of 18- 40 years with ASA physical status 1-2, 1-4 preoperative VAS, who underwent elective orthopedic extremity surgery with general anesthesia Adam Malik Hospital. Samples were then randomly divided into 2 groups with 23 subjects each. This study used a randomized controlled clinical trial double-blind. Group A received tramadol hydrochloride 2.5mg / kg / IV IV and 75 mg oral clonidine. Group B received tramadol hydrochloride 2.5mg / kg / IV and placebo. Systolic and diastolic blood pressure, pulse frequency VAS values were recorded and measured. All data were analyzed using chi-square test and the crosstab. Results : VAS value in hours and hours to 6 to 8 significant difference clinically and statistically significant in both groups, with P = 0:02 on the clock to 6 and P = 0.00 at 8 hours.Conclusion : The result showed that a combination of tramadol hydrochloride with oral clonidine produces better analgesic than tramadol hydrochloride.Keywords : tramadol hydrochloride; klonidine; visual analogue score (VAS)